Ξc(2790)+/0 and Ξc(2815)+/0 radiative decays - H. García-Tecocoatzi; A. Ramirez-Morales; A. Rivero-Acosta; E. Santopinto; C.A. Vaquera-Araujo (Physics Letters B, 2025)
In this work, we study the Ξc baryon electromagnetic decay widths within the constituent quark model formalism through an analysis of the transitions from P-wave states to ground states. We use the non-relativistic limit of the Hamiltonian for the electromagnetic interaction on keeping all the terms up to the order mj−1 and by means of a new algebraic methodology based on ladder operators. We calculate the electromagnetic decay widths analytically, for the first time, without any further approximation. Specifically, our theoretical results for the Ξc(2790)+/0 and Ξc(2815)+/0 radiative decay widths, without the introduction of any additional parameters, display a significant agreement with the recent experimental values obtained by the Belle experiment. The agreement is due to the fact that we have not introduced further approximations to simplify the calculation of the difficult convective term. Our predictions may be useful for future experiments at the Belle, BABAR, and LHC experiments.